2021
DOI: 10.2147/ccid.s315804
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Psychological Effects of Port-Wine Stain: A Review of Literature

Abstract: Introduction Port-wine stain (PWS) is a congenital malformation that does not resolve spontaneously and can cause a physiological or psychological burden to the patients. At present, most of the studies done on PWS are focused on the treatment rather than the quality of life and psychological effects of the disease. Material and Methods A comprehensive literature search was done in MEDLINE using PubMed database, Embase ® , and Cochrane. All ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…These body-hiding techniques have shown their benefits on QoL in other visible conditions as vitiligo [163,164], burn injuries [165,166], facial skin disorders (acne, atopic dermatitis, psoriasis) [167,168], infantile hemangiomas [169], and in post-surgical cancer treatment [170][171][172], which again demonstrates the impact of these conditions on body image [170,172]. Furthermore, in the case of PWS, having had an early birthmark resorption treatment (e.g., flash-lamp pulsed dye laser) has a positive effect on the subject's QoL [109]. Although many studies have shown the benefit of cosmetic camouflage in patients with skin disfigurement [173], another research has suggested that hiding any type of stigmatizing identity could have a negative impact on physical and psychological QoL [174].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These body-hiding techniques have shown their benefits on QoL in other visible conditions as vitiligo [163,164], burn injuries [165,166], facial skin disorders (acne, atopic dermatitis, psoriasis) [167,168], infantile hemangiomas [169], and in post-surgical cancer treatment [170][171][172], which again demonstrates the impact of these conditions on body image [170,172]. Furthermore, in the case of PWS, having had an early birthmark resorption treatment (e.g., flash-lamp pulsed dye laser) has a positive effect on the subject's QoL [109]. Although many studies have shown the benefit of cosmetic camouflage in patients with skin disfigurement [173], another research has suggested that hiding any type of stigmatizing identity could have a negative impact on physical and psychological QoL [174].…”
Section: Discussionmentioning
confidence: 95%
“…1 for explanations). Before going any further, it is important to point out that we recorded three recently published literature reviews specifically dedicated to inherited ichthyosis [89] and PWS [109,110]; they included studies that focused on children and adolescents and also examined psychosocial intervention-based studies. As we cannot include these articles in our current review, we will consider their results in the discussion and see if their findings are consistent with ours.…”
Section: Study Selectionmentioning
confidence: 99%
“…7 Many parents therefore favor early treatment to reduce the psychosocial stress of their children, resulting from social phobia, anxiety, and shame. 8 One example is a patient of ours who would not allow himself to be photographed from the affected side throughout his childhood. As an adult he deliberately addressed the matter publicly to encourage early treatment of children with port-wine stains so that they would not experience the same sort of emotional difficulties as he had encountered because of stigmatization.…”
Section: F I G U R Ementioning
confidence: 99%
“…Port-wine stains (PWS) birthmarks are a congenital disorder of low-flow vascular malformations of the skin, which appear at birth as pink to erythematous patches on the skin or mucous membranes [1]. The prevalence of congenital PWS is 0.3%, affecting approximately 25 million people worldwide [2]. Unlike other types of vascular birthmarks, the PWS lesion does not fade with age.…”
Section: Introductionmentioning
confidence: 99%